Microstructure and Mechanical Properties of Magnesium ZRE1 (Mg-Zn-Zr) Alloy with Rare Earth Element (Samarium) Addition - Ikhwan Shah Tisadi Tukiat, Ikhwan Shah Tisadi Tukiat; Yusuf, Nur Kamilah; Khaireez, Haikal; Sami Al-Alimi, Sami Al-Alimi; Lajis, Mohd Amri; Shamsudin, Shazarel; Ruhaizat, Nasha Emieza (jtech, 2024)
The influences of rare earth (RE) samarium (Sm) added contents to ZRE1 (Mg-Zn-Zr) magnesium (Mg) cast alloy over strength properties to be investigated. Sm at 0.5, 1.0, 1.5, and 2.0 wt.% were added separately as an alloying element to ZRE1 alloy. Optical Microscope (OM), X-ray powder diffraction (XRD), and scanning electron microscope Energy-dispersive X-ray (SEM/EDS) were used to investigate the microstructure of alloy, while mechanical properties investigated include Ultimate Tensile Strength (UTS)and Micro-Hardness (MH) tests. The result revealed that as the Sm level reached 1.5 wt.%, the grain size decreased by 20.9 %. Additionally, UTS and Yield Strength (YS) showed improvements of 8.5 % and 7.9 %, respectively, with the addition of 1.5 wt.% of Sm. In addition, elongation and hardness have been improved by 32.3 % and 10.9 % respectively at 1.5 wt.% Sm addition. Mg-Zn-Ce-Sm was formed as a new phase upon the addition of Sm and was detected via XRD analysis. The addition of Sm to the ZRE1 alloy had significant effects on the refinement of the material's microstructure, leading to an increase in its mechanical and physical properties. Therefore, the new ZRE1-RE magnesium alloy was developed.